PENGUJIAN FAMA FRENCH THREE FACTOR MODEL’S DALAM MEMPENGARUHI RETURN SAHAM STUDI KASUS PADA SAHAM LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2015-2016 - Nur Mahfudh Febriansyah; Ronny Malavia Mardani; Ahmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purpose of this study was to examine the Fama French Three Factor Model’s that is market return, firm size, and book to market ratio on stock return’s on the companies belonging to the group LQ-45. The population in this study are all companies belonging to the group LQ-45 from 2015-2016 year, totaling 51 companies. The sample used as many as 51 sample’s and which meet the requirements of as many as 40 companies. The sampling technique in this study by using purposive sampling technique, while the method of data analysis in this study using multiple linier regression analysis. Results from this study provide empirical evidence that the market return, firm size, and book to market ratio have a significant effect on stock returns. Market return have a positive and significant effect on stock returns. Firm size have a positive but not significant effect on stock returns. Book to market ratio have a positive but not significant effect on stock returns. Keywords: firm size, book to market ratio, returns